2014
DOI: 10.1080/10454446.2013.845866
|View full text |Cite
|
Sign up to set email alerts
|

Factors Influencing Young Consumers’ Acceptance of Genetically Modified Food in India

Abstract: We analyzed the determinants of acceptance of genetically modified food (GMF) by using the probit model. In this study, we found that around 41% of the students are willing to buy GMF, and acceptance of GMF is less in female respondents than male respondents. The findings indicate that in India, benefit perception of GMF outweighed the risk perception. We also found that respondents' trust in international organizations for truthful information has a positive and significant influence on acceptance of GMF.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
14
1
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(16 citation statements)
references
References 47 publications
0
14
1
1
Order By: Relevance
“…However, the comparison about the degree of the influence in reducing perceived risks across groups revealed interesting results both conceptually and managerially. Past studies reported that people have dread and unknown perceptions about GMF and have empirically tested the usefulness of improved knowledge [ 26 , 36 , 61 ].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…However, the comparison about the degree of the influence in reducing perceived risks across groups revealed interesting results both conceptually and managerially. Past studies reported that people have dread and unknown perceptions about GMF and have empirically tested the usefulness of improved knowledge [ 26 , 36 , 61 ].…”
Section: Discussionmentioning
confidence: 99%
“…Prior literature on science communication advocates that in case of promoting debatable and innovative technologies, such as GM food, providing scientific literacy is an effective communication strategy [ 36 ]. This will enhance the acceptance of such technologies among the public by decreasing their risk perceptions.…”
Section: Literature Review and Theoretical Underpinningmentioning
confidence: 99%
See 1 more Smart Citation
“…Information from reputable international organisations such as the World Health Organization, and the Food and Agriculture Organization has also been found to have a positive influence on consumer trust (Kajale and Becker 2015) believing that these organisations are likely to provide responsible advice on food safety (Kajale and Becker 2015).…”
Section: Previous Literature In Relation To Trust In Foodmentioning
confidence: 99%
“…10. The rationale for the study, "Factors influencing young consumers' acceptance of genetically modified food in India" (Kajale and Becker 2015), is built on theory of reasoned action (Fishbein and Ajzen 1975). The authors used the following variables to predict consumer acceptant of genetically modified food (GMF): sociodemographic variables, attitude modern technology (dummy), GMF knowledge (dummy), risk perceptions, benefit perceptions, concerns, and trust for truthful information about GMF.…”
Section: An Extended Search On Scopus Databasementioning
confidence: 99%